Implementation of Nurse Therapeutic Communication in the Inpatient Room - Darmi Arda; Maria Kurni Menga; Yuriatson Yuriatson (Edukasi Ilmiah Indonesia, 2023)
Therapeutic communication is one of the important components of nursing practice in the treatment room. It involves the exchange of information, empathy, and support between nurses and patients. The study aims to determine the implementation of nurse-therapeutic communication in the inpatient room. Quantitative research design with descriptive survey approach. The result is that the implementation of nurse therapeutic communication in the pre-orientation, orientation, work, and termination phases is carried out partially. It can be concluded that the implementation of nurse therapeutic communication in the pre-orientation phase, orientation phase, work phase, and termination phase is carried out partially. The influence of communication dynamics in the application of therapeutic communication shows that nurses carrying out therapeutic communication in the pre-orientation phase are only partially carried out